DNA breaks in hypermutating immunoglobulin genes: evidence for a break-and-repair pathway of somatic hypermutation. - Kong, Q (2001)
To test the hypothesis that immunoglobulin gene hypermutation in vivo employs a pathway in which DNA breaks are introduced and subsequently repaired to produce mutations, we have used a PCR-based assay to detect and identify single-strand DNA breaks in lambda1 genes of actively hypermutating primary murine germinal center B cells. We find that there is a two- to threefold excess of breaks in lambda1 genes of hypermutating B cells, relative to nonhypermutating B cells, and that 1.3% of germinal center B cells contain breaks in the lambda1 gene that are associated with hypermutation. Breaks were found in both top and bottom DNA strands and were localized to the region of lambda1 that actively hypermutates, but duplex breaks accounted for only a subset of breaks identified. Almost half of the breaks in hypermutating B cells occurred at hotspots, sites at which two or more independent breaks were identified. Breaksite hotspots were associated with characteristic sequence motifs: a pyrimidine-rich motif, either RCTYT or CCYC; and RGYW, a sequence motif associated with hypermutation hotspots. The sequence motifs identified at breaksite hotspots should inform the design of substrates for characterization of activities that participate in the hypermutation pathway.